O apoio técnico administrativo aos departamentos didáticos em uma universidade: o caso da secretaria unificada dos departamentos SUDEP/UFSM campus Frederico Westphalen - Piovesan, Márcio Luis (2016)
This study aimed to analyze the system adopted in the administrative processes of the Unified Secretariat of the Departments - SUDEP the Federal University of Santa Maria - Campus Frederick. As a new department structure, different from that adopted in the university headquarters, where all of the registry servers meet the demands of all campus departments, there may be some difficulties in the execution of daily processes. In order to identify possible difficulties and propose subsidies to minimize them or ban them was conducted this study. The study focused on the processes carried out in SUDEP and had as subjects surveyed the employees of this department. The methodology used was descriptive qualitative research, with data collection using questionnaires and semi-structured interviews applied to the SUDEP servers to identify the processes that are performed in the office as well as those requiring formalization and those who do not require formalization. Using these data proceeded to the classification of processes that require formalization as an analytical category the degree of difficulty and the execution time in primary and critics using the model proposed by Valle and Oliveira (2009). From a total of fourteen identified processes that require formulation, five were classified as primary nine as critical. Thus, flowcharts were created, it was possible to clearly demonstrate the flow steps of each process follows during its development, providing subsidies for easy understanding and application for the development of formalized guidelines on standard procedure of the processes considered critical by the current server this sector. Moreover, it was possible to identify all considered critical processes is related to the planning of the institution, where some have characteristics related to strategic planning and other related operational planning. It is concluded that research achieved its objectives by identifying the processes developed in SUDEP that present greater difficulties in their development and proposing subsidies in the form flowcharts that will serve to enhance the development of processes, contributing to the achievement of institutional objectives.